Pengembangan Dan Uji Usability Aplikasi Pemilu Legislatif 2019 Kota Tangerang Selatan Menggunakan Metode Prototyping Berbasis Android - Syifa Shabrina Siregar; Agi Putra Kharisma; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the reality of election in Indonesia, they still have many problems in terms of voting and counting especially in a new city such as the City of South Tangerang. This deficiency is also related to the implementation of elections that are still conventional in the era of technological development. One form of technological development is seen in smartphone use. In Indonesia, 80% of smartphone users use the Android operating system. Against this background, the application of the 2019 South Tangerang City Legislative Election was made using the prototyping method. This application is the result of brainstorming with stakeholders to get features that are in accordance with the needs described by stakeholders, the Dinas Komunikasi dan Informatika of South Tangerang City and Komisi Pemilihan Umum of South Tangerang City, then the results of the brainstorming are modeled into prototypes and tested regularly to the user to find out if there are still deficiencies found in the application design. The purpose of this application is to get information on how to make the appropriate application for the Election and the citizens of South Tangerang City and test its usability level as one of the aspects of the Election application that was appointed in this study. Before being used by users of this application through the blackbox test to find out whether all the features in the application are functioning properly. While usability itself is assessed through the SUPR-Qm questionnaire to show that the application can be well received by users in various ages. The results of using prototype modeling after blackbox and usability testing are eight features of the application that works properly and the usability level is in category C, when it converted the result of usability level means good and the application can be accepted by citizen of South Tangerang City.